PEMANFAATAN LARVA LALAT BLACK SOLDIER FLY (Hermetia illucens) UNTUK PEMBUATAN PUPUK KOMPOS PADAT DAN PUPUK KOMPOS CAIR - Prisilia Eka Kusumawati; Yusriani Sapta Dewi; Rofiq Sunaryanto (JURNAL TECHLINK, 2020)
Composting is a form of decomposing organic matter with the help of organisms for bioconversion. The composting process requires several requirements to produce good quality compost, namely water content, pH and nutrient availability which is reflected in the C / N ratio. One type of insect larvae that can be used as an element of organism is the Black Soldier Fly (BSF) insect. The effort to recycle organic waste involving Black Soldier Fly (BSF) insect larvae is a new paradigm in the management of organic waste as decomposers or decomposers of organic waste. The result of the conversion of organic waste into solid compost fertilizer has a moisture content value that exceeds quality standards, C-organic value and C / N ratio which is below the quality standard, has a basic pH, and macro nutrients (N + P2O5 + K2O) located in the Permentan quality standard No. 261 / KPTS / SR.30 / M /4/2019, while for liquid compost fertilizer the value of C-organic and macro nutrients (N + P2O5 + K2O) is in Permentan quality standard No.261 / KPTS / SR.30 / M / 4/2019.